PENGARUH KETERSEDIAAN ANGGARAN TERHADAP TINGKAT KEPUASAN MASYARAKAT TAHUN ANGGARAN 2019 SAMPAI DENGAN 2021 DI PANTI SOSIAL BINA WANITA MELATI PROVINSI KALIMANTAN SELATAN - NITA, NOVIDA HERLIA (JURNAL KINDAI, 2023)
Abstract: Budget is an important thing for public service providers. Budget as a guideline for action in the unit of revenue and expenditure plan in units of money which is arranged systematically for a period. The level of community satisfaction is obtained through quantitative and qualitative measurements of public opinion in obtaining the services of the apparatus for providing public services. This measurement is called the Community Satisfaction Index. As an effort to improve the quality of public services, it is necessary to conduct an evaluation through the Community Satisfaction Survey. With the available budget, government agencies should provide excellent service. This study is a quantitative study that seeks to examine the effect of the budget on people's satisfaction. Budget Sources and Budget Allocations have no partial effect on Community Satisfaction, Budget Management has a partial effect on Community Satisfaction, and Budget Sources, Budget Allocations, and Budget Management have a simultaneous effect on Community Satisfaction at the Bina Wanita Melati Social Institution in South Kalimantan Province. This shows that if budget management is carried out properly, it will have a positive impact on community satisfaction. Keywords: Budget, Budget Availability, Community Satisfaction